Metavirome characterization in Anopheles darlingi from three different geographical regions of Colombia (2022)
ABSTRACT: The association between Anopheles and viruses is relevant because its potential utility in biological vector control in addition, it has implications for public health given that some Anopheles species might even spread viruses 1 2 The recent emergence of metagenomics, driven by advances in massive sequencing technologies, has allowed virome characterization in different host types including mosquitoes 3 Despite its relevance, the viral component has been little explored in the Neotropical species of the Anopheles genus, including Anopheles dalringi the principal malaria vector in the Neotropics and a primary vector in Colombia Therefore, the aim of this study was to characterize the metavirome profile in An darlingi from important malaria endemic regions of Colombia.